Barrett's oesophagus length is established at the time of initial endoscopy and does not change over time: results from a large multicentre cohort. Issue 12 (4th February 2015) - Moawad, Fouad J; Young, Patrick E; Gaddam, Srinivas; Vennalaganti, Prashanth; Thota, Prashanthi N; Vargo, John; Cash, Brooks D; Falk, Gary W; Sampliner, Richard E; Lieberman, David; Sharma, Prateek
Abstract : Objective: It is unclear whether Barrett's oesophagus (BO) length changes over time or whether the full length of the segment is established at the onset of disease recognition. The objectives of this study were to evaluate the association of age and BO length and to evaluate the changes in BO length over time. Design: This is a prospective, multicentre cohort study involving patients with BO from five centres. Patients were divided into groups based on the decade of initial diagnosis of BO. The mean BO length and the mean change in BO length were calculated for each age decade. The mean change in BO length was also calculated between the index endoscopy and the last surveillance endoscopy. Results: 3635 patients with BO were included in the study: 87.8% men, 92.8% Caucasians, mean age 60.9 years and mean BO length 3.5 cm. The mean change in BO length was 0.9 cm. The mean BO length did not significantly change for each age category: <30 years (4.6 cm), 30–39.9 years (3.2 cm), 40–49.9 years (3.1 cm), 50–59.9 years (3.1 cm), 60–69.9 years (3.6 cm), 70–79.7 (4.0 cm) and >80 years (4.5 cm), p=0.47. On subgroup analysis of patients with non-dysplastic BO who had at least 1 year of endoscopic follow up, there was a significant decrease in mean change in BO length across age categories ranging from +1.7 to −0.8 cm, p=0.03. Conclusions: There was no significant difference in BO length by age category in decades. In addition, the change in BO length from index to follow-up endoscopy was similar among patients >30 years. These findings suggest that a patient's BO segment length attains its full extent by the time of the initial endoscopic examination.